Corneal transplantation activity in Catalonia, Spain, from 2011 to 2018: Evolution of indications and surgical techniques. - Noelia Sabater-Cruz; Marc Figueras-Roca; Lydia Padró-Pitarch; Jaume Tort; Ricardo P Casaroli-Marano (PLoS ONE)
Purpose To report corneal transplant activity carried out in Catalonia (Spain) and the evolving indications for keratoplasty over an 8-year period. Methods Annual reports from the Catalan Transplant Organization, Spain, on corneal graft indications and techniques from 2011 to 2018 were reviewed. Results A total of 9457 keratoplasties were performed in Catalonia, from January 2011 to December 2018. The most frequent indications were bullous keratopathy (BK; 20.5%), Fuchs endothelial dystrophy (FED; 17.9%), re-graft (13.7%), and keratoconus (11.3%). Penetrating keratoplasty (PKP) accounted for 63.4% of all performed keratoplasties. Since the introduction of eye bank precut tissue for Descemet stripping automated endothelial keratoplasty (DSAEK) in 2013 and for Descemet membrane endothelial keratoplasty (DMEK) in 2017 the number of endothelial keratoplasties has drastically increased. An increasing trend of posterior lamellar techniques over the total of keratoplasties was found (p<0.001). Endothelial keratoplasties for different endothelial diseases indications (BK, FED, and re-graft), also showed and increasing trend (p<0.001). DMEK is the technique with the highest increase (statistically significantly different from linearity) over other endothelial keratoplasties in FED (p<0.001) but not in BK (p = 0.67) or re-grafts (p = 0.067). Conclusion Endothelial diseases represented the top indication for keratoplasty over the 8-year period. PKP is still the most used technique in Catalonia, but endothelial keratoplasties and especially DMEK showed a significant increasing trend over the last years. This is congruent with the main rationale nowadays for keratoplasties: to customize and transplant as less tissue as possible. Therefore, the availability of precut tissue could have definitely enforced such approach.